The Influence of the Posonan Tradition at the Pathok Negoro Mlangi Mosque on Mad'u Behavior - Imawan, Dzulkifli Hadi; Al Ghazali, Muhammad Nurkhalid (Munazzama: Journal of Islamic Management and Pilgrimage, 2021)
The Pathok Negoro Mosque is one of the mosques that plays an important role in maintaining the religious understanding of the surrounding community. This mosque is a cultural heritage protected by the Yogyakarta government. In the month of Ramadhan (Posonan) this mosque has a religious tradition in the form of a yellow book study filled by local scholars who are scheduled every afternoon and evening. Therefore, this research needs to be carried out to explore the Posonan religious tradition in the Pathok Negoro Mlangi Mosque and its influence on religious understanding in the surrounding community. This research includes descriptive qualitative with a historical approach to reveal the content of the object under study. Posonan religious traditions at the Pathok Negoro Mlangi Mosque have influenced the mad’u in community that increasing the spirit of increasing worship, the spirit of studying, and the spirit of having Islamic character as well as strengthening social ties and a sense of responsibility.